2022
DOI: 10.1515/tjb-2021-0180
|View full text |Cite
|
Sign up to set email alerts
|

Kefir protects the liver against high fructose corn syrup induced phosphodiesterase hyperactivity

Abstract: Objectives Phosphodiesterases (PDEs) mediate several physiological activities, and alterations in PDE expressions might cause conflicts between functional and clinical effects. This study clarifies the eventual relationship between the hepatic insulin resistance-associated signaling elements and PDEs together with inflammatory markers and investigates the role of kefir in the treatment. Methods Male Wistar rats were grouped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Probiotics are a mixture of beneficial bacteria and/or yeasts that occur naturally in the human body, and when combined with prebiotics, they have been shown to treat a variety of ailments such as allergies, gastrointestinal problems, and inflammation [Markowiak & Śliżewska, 2017]. Kefir, a fermented milk product classified as source of probiotics, comprises lactic and acetic acid bacteria in a polysaccharide matrix [Rosa et al, 2016] and has been found to have anti-viral [Hamida et al, 2021], anti-inflammatory [Akar et al, 2021;Pektaş et al, 2022], and anti-allergic properties [Barros et al, 2021]. It has also been demonstrated to prevent problems brought on by fructose or high-fructose corn syrup (HFCS) ingestion [Akar et al, 2021;Chen et al, 2016;Ekici et al, 2022a;Rosa et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are a mixture of beneficial bacteria and/or yeasts that occur naturally in the human body, and when combined with prebiotics, they have been shown to treat a variety of ailments such as allergies, gastrointestinal problems, and inflammation [Markowiak & Śliżewska, 2017]. Kefir, a fermented milk product classified as source of probiotics, comprises lactic and acetic acid bacteria in a polysaccharide matrix [Rosa et al, 2016] and has been found to have anti-viral [Hamida et al, 2021], anti-inflammatory [Akar et al, 2021;Pektaş et al, 2022], and anti-allergic properties [Barros et al, 2021]. It has also been demonstrated to prevent problems brought on by fructose or high-fructose corn syrup (HFCS) ingestion [Akar et al, 2021;Chen et al, 2016;Ekici et al, 2022a;Rosa et al, 2016].…”
Section: Introductionmentioning
confidence: 99%